Does over-dominance of Bambusa bambos (L.) Voss. alter abundance and richness of Arbuscular Mycorrhizal fungal community in forests? - Fathima Mafaziya (Ceylon Journal of Science, 2019)
Some areas under the Tropical Moist Evergreen Forests (TMEF), the major forest type in the Intermediate Zone of Sri Lanka, are heavily dominated by a native bamboo species, Bambusa bambos (L.) Voss. altering the hierarchical status and structure. The study evaluated whether the over-abundance of B. bambos has modified the arbuscular mycorrhizal fungal (AMF) communities in soil. Soil samples collected from bamboo-dominated (BM) and non-bamboo (NB) forest patches in three different locations viz., Moragolla, Maragomuwa and Galboda, were enumerated for AMF spores using wet sieving and decanting method. A total of 1,577 and 898 AMF spores were documented from BM and NB forest patches, respectively. A total of 14 different morphotypes belonged to the genera, Glomus, Scutellospora, Gigaspora and Acaulospora, were identified. Glomus was the dominant genus in all study sites, while Acaulospora the least. The mean abundance and richness of AMF spores were higher in BM than in NB, with the most notable difference observed at Maragomuwa. These site-specific variations may perhaps due to the differences in vegetation characteristics, edaphic properties and disturbance regimes. However, the community structure of AMF showed no conspicuous modifications due to the over-abundance of B. bambos. The findings reiterated the general understanding that any changes to the above-ground vegetation may incur impacts on the AMF. However, AMF community structure shows resilience to influences imposed by the dominance of a single species.